2020
DOI: 10.1192/j.eurpsy.2020.74
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of birth weight on brain volumes and depression: An observational and genetic study using UK Biobank cohort

Abstract: Background. Birth weight influences not only brain development, but also mental health outcomes, including depression, but the underlying mechanism is unclear. Methods. The phenotypic data of 12,872–91,009 participants (59.18–63.38% women) from UK Biobank were included to test the associations between the birth weight, depression, and brain volumes through the linear and logistic regression models. As birth weight is highly heritable, the polygenic risk scores (PRSs) of birth weight were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, frequently women with MB tend not to start or discontinue breastfeeding very early and have a significantly reduced interaction with the newborn ( 28 , 29 ). All studies converge on the fact that, if untreated, MB symptoms can have serious consequences on women's and infants' mental health ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, frequently women with MB tend not to start or discontinue breastfeeding very early and have a significantly reduced interaction with the newborn ( 28 , 29 ). All studies converge on the fact that, if untreated, MB symptoms can have serious consequences on women's and infants' mental health ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also reported lower surface areas in lingual, fusiform, parahippocampal gyrii (Couvy-Duchesne et al, 2018) and subcallosal regions (Wei et al, 2020), as well as cortical volume reduction in prefronal cortex, orbitalfrontal cortex (Grieve et al, 2013), subcallosal regions (Wei et al, 2020), temporal pole, insula lobe (Amidfar et al, 2020) and subgenual anterior cingulate cortex (Niida et al, 2019). Although some research indicated MDD-related reduction in thalamus (Schmaal et al, 2016;Webb et al, 2014;Ye et al, 2020), amygdala (Qi et al, 2018) and hippocampus (Nugent et al, 2013), the MDD case-control volumetric differences in subcortical regions have been found to be insignificant in some other studies (Bos et al, 2018;Shen et al, 2017). Furthermore, white matter microstructure (Chen et al, 2017;Shen et al, 2017;van Velzen et al, 2020), functional connectivity (Qiao et al, 2020;Ran et al, 2020) and abnormalities were also found in MDD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The neurobiological mechanisms underlying sex-differences in aggression related to BW are not elucidated by this study or to our knowledge any study; however, fetal neurodevelopment differs by offspring sex [4850] and is in turn affected by BW [51]. A study from the UK biobank suggested that BW-PGS and measured BW affected adult depression through various brain regions, and that these effects differed by offspring sex [52]. Similarly, a recent study found that caudate nucleus volumes in neonates had opposite associations to polygenic scores for adult depression providing evidence for sex-dimorphic relationships between fetal development and mental health [53].…”
Section: Discussionmentioning
confidence: 99%